Study on Milling Characteristics and Surface Integrity of AZ31B Magnesium Alloy - Zhang, Pengchong; Du, Mingxuan; Wang, Rongjun; Ohashi, Kazuhito (Transactions of the Indian Institute of Metals, 2024)
Magnesium alloy material is the lightest practical structural metal in the industry, making milling work pieces perfectly suitable for precision machining in automotive and aerospace fields. The purpose of milling is to obtain work pieces that meet the requirements in terms of accuracy and quality, so it is important to ensure the surface integrity of the work piece during the machining process. Surface integrity factors, such as residual stress, has been proved to remarkably influence the functional performance of magnesium alloy, including corrosion resistance, fatigue strength, geometric stability, and fatigue life. In this study, the effect of milling parameters on the surface integrity of AZ31B magnesium alloy was summarized, including the influence of milling parameters on milling force, milling temperature, and residual stress. These influence laws play a guiding role in the optimization of machining parameters and can promote the development of machining of AZ13B magnesium alloy.